Minimally invasive surgical correction technique of Pectus Arcuatum, case report of an innovative method for a rare chest wall malformation (Jerusalem technique) - Moshe, Daniella; Salhab, Anas; Shimonov, Mordechai; Abu Akar, Firas (Frontiers in Surgery, 2025)
Pectus Arcuatum (PA) is a rare anterior chest wall deformity characterized by a deformation with potential psychological impact on patients and combining features of both pectus carinatum and pectus excavatum. Traditional corrective methods involve open surgical techniques, such as sternotomy, which often result in significant surgical scars. This case report presents two patients who underwent successful minimally invasive correction of PA using a modified sandwich method, referred to as the Jerusalem Technique. The innovative approach involved bilateral thoracoscopic-guided osteotomies and placement of one or more support bars, all performed through lateral incisions without midline exposure. Both patients demonstrated excellent cosmetic and functional outcomes, minimal postoperative pain, and no complications. As many patients seek surgery for cosmetic concerns, there is a growing interest in minimally invasive approaches, this technique offers an effective alternative to traditional open surgery, representing fully minimally invasive surgical correction for PA.